Lipocalin-2 Deficiency Reduces Oxidative Stress and Neuroinflammation and Results in Attenuation of Kainic Acid-Induced Hippocampal Cell Death - Hyun Joo Shin; Eun Ae Jeong; Jong Youl Lee; Hyeong Seok An; Hye Min Jang; Yu Jeong Ahn; Jaewoong Lee; Kyung Eun Kim; Gu Seob Roh (MDPI AG, 2021)
The hippocampal cell death that follows kainic acid (KA)-induced seizures is associated with blood-brain barrier (BBB) leakage and oxidative stress. Lipocalin-2 (LCN2) is an iron-trafficking protein which contributes to both oxidative stress and inflammation. However, LCN2's role in KA-induced hippocampal cell death is not clear. Here, we examine the effect of blocking LCN2 genetically on neuroinflammation and oxidative stress in KA-induced neuronal death. LCN2 deficiency reduced neuronal cell death and BBB leakage in the KA-treated hippocampus. In addition to LCN2 upregulation in the KA-treated hippocampus, circulating LCN2 levels were significantly increased in KA-treated wild-type (WT) mice. In LCN2 knockout mice, we found that the expressions of neutrophil markers myeloperoxidase and neutrophil elastase were decreased compared to their expressions in WT mice following KA treatment. Furthermore, LCN2 deficiency also attenuated KA-induced iron overload and oxidative stress in the hippocampus. These findings indicate that LCN2 may play an important role in iron-related oxidative stress and neuroinflammation in KA-induced hippocampal cell death.